Case Report: Visceral leishmaniasis misdiagnosed as systemic lupus erythematosus in a 36-year-old migrant worker - Li-Ping Sheng; Bo-Zhi Lin; Li-Na Han; Gui-Qiang Wang; Gui-Qiang Wang; Feng-Qin Hou; Feng-Qin Hou (Frontiers in Medicine)
Visceral leishmaniasis (VL), also known as kala-azar, is an often-neglected tropical disease caused by Leishmania donovani. It is endemic in certain regions of China, including Shanxi Province. This case report describes a 36-year-old female migrant worker who regularly travels between Shanxi Province, her hometown and Zhongshan, Guangdong Province. She presented with prolonged fever, splenomegaly, pancytopenia and high title anti-nuclear antibodies. She was initially diagnosed with systemic lupus erythematosus (SLE) and associated polyclonal gammopathy. Her condition failed to improve with corticosteroids and immunosuppressants. Further evaluation revealed VL, confirmed by bone marrow smear and molecular testing. Treatment with liposomal amphotericin B led to prompt clinical resolution. This case highlights the importance of obtaining travel history and considering parasitic infections in patients with refractory fever and splenomegaly.